Enhanced decoupling current scheme with selective harmonic elimination pulse width modulation for cascaded multilevel inverter based static synchronous compensator - Law, Kah Haw (2015)
This dissertation is dedicated to a comprehensive study and performance analysis of the transformer-less Multilevel Cascaded H-bridge Inverter (MCHI) based STATic synchronous COMpensator (STATCOM). Among the shunt-connected Flexible AC Transmission System (FACTS) controllers, STATCOM has shown extensive feasibility and effectiveness in solving a wide range of power quality problems. By referring to the literature reviews, MCHI with separated DC capacitors is certainly the most versatile power inverter topology for STATCOM applications. However, due to the ill-defined transfer functions, complex control schemes and formulations were emerged to achieve a low-switching frequency high-bandwidth power control. As a result, adequate controller parameters were generally obtained by using trial and error method, which were practically ineffective and time-consuming. In this dissertation, the STATCOM is controlled to provide reactive power (VAR) compensation at the Point of Common Coupling (PCC) under different loading conditions. The goal of this work is to enhance the performance of the STATCOM with the associated proposed control scheme in achieving high dynamic response, improving transient performance, and producing high-quality output voltage waveform. To evaluate the superiority of the proposed control scheme, intensive simulation studies and numerous experiments are conducted accordingly, where a very good match between the simulation results and the experimental results is achieved in all cases and documented in this dissertation.